Rural EFL Teachers’ Perceptions of Promoting Learner Autonomy in Indonesia’s Independent Curriculum - Amalo, Bonik Kurniati; Lehar, Laurensius (Politeknik Negeri Bali, 2025)
As Indonesia’s education system adopts the Independent Curriculum, the promotion of learner autonomy has attained renewed importance, particularly in English language education. While the theoretical advantages of learner autonomy are well-established, empirical research examining how EFL teachers in rural Indonesian contexts perceive and implement this concept remains limited. This study looked into the views and self-reported practices of 40 in-service EFL teachers from rural schools in Kupang Regency within the framework of the Independent Curriculum. Data were obtained using structured questionnaires and open-ended reflections. The findings indicate that although teachers generally express positive attitudes toward the value of learner autonomy, many participants demonstrated limited theoretical understanding and lacked the pedagogical strategies necessary for fostering autonomy in their classrooms. While a majority believed that promoting learner autonomy is feasible, their justifications often relied on general assumptions—such as potential improvements in language proficiency—rather than a concrete understanding of how autonomy can be integrated into classroom practice. These findings highlight the need for targeted professional development that equips teachers with both conceptual knowledge and practical tools aligned with the goals of the Independent Curriculum.